Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2018
DOI: 10.1159/000493938
|View full text |Cite
|
Sign up to set email alerts
|

Prenatal Growth in Fetuses with Isolated Cyanotic and Non-Cyanotic Congenital Heart Defects

Abstract: Background: Fetal growth may vary significantly in different congenital heart defects (CHDs). Objectives: To investigate prenatal growth of CHD fetuses and its correlation with classifications based upon expected oxygen delivery to the fetal brain or structural findings. Methods: Seventy-nine euploid fetuses with isolated CHD were recruited prospectively and categorized by the expected oxygen supply to the brain (low, intermediate, and high) or by the expected arterial mixing considering two categories (cyanot… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
17
1

Year Published

2020
2020
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 23 publications
(23 citation statements)
references
References 29 publications
2
17
1
Order By: Relevance
“…However, the onset of reduced volumetric brain growth is not limited to the third trimester as many studies have also found reductions in fetal head biometry beginning in the second trimester in both major and minor CHD (28)(29)(30)(31)(32), though more prominent in fetuses with single ventricle physiology (SVP), HLHS, TOF, and TGA. More compellingly, fetuses with CHD, especially cyanotic subtypes, have demonstrated abnormal fetal head biometry in the first trimester (33) and as early as 11-14 GW in fetuses with left heart hypoplasia (34), suggesting a potential genetic contribution towards abnormal brain development in CHD.…”
Section: Total and Regional Brain Sizementioning
confidence: 99%
“…However, the onset of reduced volumetric brain growth is not limited to the third trimester as many studies have also found reductions in fetal head biometry beginning in the second trimester in both major and minor CHD (28)(29)(30)(31)(32), though more prominent in fetuses with single ventricle physiology (SVP), HLHS, TOF, and TGA. More compellingly, fetuses with CHD, especially cyanotic subtypes, have demonstrated abnormal fetal head biometry in the first trimester (33) and as early as 11-14 GW in fetuses with left heart hypoplasia (34), suggesting a potential genetic contribution towards abnormal brain development in CHD.…”
Section: Total and Regional Brain Sizementioning
confidence: 99%
“…6,7 Moreover, fetuses with CHD (especially within the cyanotic group) present abnormal pattern of prenatal growth with lower birthweight and head size. 8 Signs of placental dysfunction are already evident in the first trimester of pregnancy with lower serum levels of pregnancy-associated plasma protein A (PAPP-A) and placental growth factor (PlGF) in CHD pregnancies as compared to controls. 1 Such placental impairment might be associated with underperfusion resulting in an increase in the uterine artery pulsatility index (UtA-PI) in mid-pregnancy in CHD pregnancies.…”
Section: Introductionmentioning
confidence: 99%
“…Abnormal placental cord insertion is more common in placentas from pregnancies with fetal CHD 6,7 . Moreover, fetuses with CHD (especially within the cyanotic group) present abnormal pattern of prenatal growth with lower birthweight and head size 8 …”
Section: Introductionmentioning
confidence: 99%
“…2 Reduced cerebral oxygen and nutrient delivery, particularly inadequate glucose supply in CHD fetuses, are responsible for impaired brain development during fetal life, and even the most contemporary publications stress this in the third trimester of pregnancy, 3 while it has been well established on ultrasound (US) that fetuses with CHD have a smaller head circumference (HC) and biparietal diameter from the second trimester of pregnancy onward and, recently, that those with cyanotic CHD have smaller HC from the first trimester, as early as 11-14 gestational weeks (GW), compared to age-matched controls. 4 Magnetic resonance imaging (MRI), obviously, provides more detailed insight into the brain structure and volume than US; however, it is more affected by fetal motion. MRI allows for fetal brain segmentation and measurement of structures' volumes, and three-dimensional (3D) volumetry is performed mostly in the third trimester, preferably near the end of pregnancy, when the fetus is least mobile and the segmentation is easiest to carry out.…”
mentioning
confidence: 99%
“…Reduced cerebral oxygen and nutrient delivery, particularly inadequate glucose supply in CHD fetuses, are responsible for impaired brain development during fetal life, and even the most contemporary publications stress this in the third trimester of pregnancy, 3 while it has been well established on ultrasound (US) that fetuses with CHD have a smaller head circumference (HC) and biparietal diameter from the second trimester of pregnancy onward and, recently, that those with cyanotic CHD have smaller HC from the first trimester, as early as 11–14 gestational weeks (GW), compared to age‐matched controls 4 …”
mentioning
confidence: 99%